Ecology of Affect Intensive Milieus and Contingent Encounters - Angerer, Marie-Luise (meson press, 2017)
The way we conceive the human today is particularly affected by the shifts in media technology during the 20th century. Affect emerges as the new liminal concept that renders the body compatible in novel ways with the technology and politics of media. By ways of a relational reorganization the organic end technological life is condensed in a new, intense way to an ecology of affects.